Intertekstualitas Puisi “Di Jembatan Mirabeau” karya Agus R. Sarjono dan Le Pont Mirabeau karya Guillaume Apollinaire - Septoriana Maria Nino (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
This research contains an intertextual study of poem “Di Jembatan Mirabeau” by Agus R. Sarjono and Le Pont Mirabeau by Guillaume Apollinaire. Both of these poems describe the same object, Mirabeau bridge. The purpose of this research is to determine the intertextuality between these two poems. The method and approach that used in this reserch are library method and intertextuality approach. The writer found several things that show the similarities and differences of these two poems. The similarities are found through the setting, structure of sentences, and point of view. While the differences are found through the language, time, final rhymes, and typography. The result showed that these poems have same meanings and expansion, conversion, modification, and exclution.